Morphological and polymerase chain reaction-restriction fragment lenght polymorphism characterization of Biomphalaria kuhniana and Biomphalaria amazonica from Colombia (2002)
ABSTRACT: In Colombia, five Biomphalaria planorbid species are known: B. kuhniana, B. straminea, B. peregrina, B. canonica and B. oligoza(var. B. philippiana). Among them, B. straminea is intermediate host of Schistosoma mansoni and B. peregrina has been found to be experimentally susceptible to this parasite. B. straminea is commonly confused with B. kuhniana and they have been clustered together with B. intermedia in the complex named B. straminea. The difficulties involved in the specific identification, based on morphological data, have motivated the use of new techniques as auxiliary tools in cases of inconclusive morphological identification of such planorbid. In the present study, five Biomphalaria populations from the Colombian Amazon region and from Interandian Valleys were morphologically identified and characterized by polymerase chain reaction-restriction fragment lenght polymorphism directed at the internal transcribed spacer region of the rRNA gene, followed by digestion of the generated fragment with restriction enzymes (DdeI, AluI, RsaI, MvaI and HaeIII). Known profiles of the Brazilian species B. straminea, B. peregrina, B. kuhniana, B. intermedia and B. amazonica, besides B. kuhniana from Colombia, were used for comparison. The five populations under study were morphologically and molecularly identified as B. kuhniana and B. amazonica.